Missing May - Rylant, Cynthia (New York : Orchard Books, 1992)
After the death of the beloved aunt who has raised her, twelve-year-old Summer and her uncle Ob leave their West Virginia trailer in search of the strength to go on living.
"A Richard Jackson book"--Half t.p.
G5
Keywords: Death -- Fiction; Grief -- Fiction; Aunts -- Fiction; West Virginia -- Fiction